2023
DOI: 10.3389/fmed.2023.1192969
|View full text |Cite
|
Sign up to set email alerts
|

Hospital length of stay prediction tools for all hospital admissions and general medicine populations: systematic review and meta-analysis

Swapna Gokhale,
David Taylor,
Jaskirath Gill
et al.

Abstract: BackgroundUnwarranted extended length of stay (LOS) increases the risk of hospital-acquired complications, morbidity, and all-cause mortality and needs to be recognized and addressed proactively.ObjectiveThis systematic review aimed to identify validated prediction variables and methods used in tools that predict the risk of prolonged LOS in all hospital admissions and specifically General Medicine (GenMed) admissions.MethodLOS prediction tools published since 2010 were identified in five major research databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Hospital length-of-stay and admission frequency are ubiquitous metrics in biomedical research, functioning as indicators for disease burden and health care expenditures [ 1 5 ].There is considerable interest in identifying factors related to either prolonged or frequent hospitalization [ 6 , 7 ], with subsequent implementation in predictive models and risk stratification tools. Although several dimensions have been assessed, the utility of attributes other than age and co-morbidity ranges between contextual and ambiguous [ 8 , 9 ]. Furthermore, while alcohol consumption and the use of psychoactive prescription medication is frequently encountered in clinical practice, data regarding their interaction with length-of-stay and admission frequency is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital length-of-stay and admission frequency are ubiquitous metrics in biomedical research, functioning as indicators for disease burden and health care expenditures [ 1 5 ].There is considerable interest in identifying factors related to either prolonged or frequent hospitalization [ 6 , 7 ], with subsequent implementation in predictive models and risk stratification tools. Although several dimensions have been assessed, the utility of attributes other than age and co-morbidity ranges between contextual and ambiguous [ 8 , 9 ]. Furthermore, while alcohol consumption and the use of psychoactive prescription medication is frequently encountered in clinical practice, data regarding their interaction with length-of-stay and admission frequency is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Even among patients with similar severity of illness, the duration of hospitalization can serve as an indicator of the overall quality of diagnosis, treatment and care provided (9). Presently, research on predicting hospitalization risks at the global level remains limited, with a particularly paucity of studies in this domain in China (10,11). Moreover, the existing studies have revealed signi cant heterogeneity in various aspects, such as social structure, medical policies and levels of diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%